Stimulus-responsive tea polyphenols as nanocarrier for selective intracellular drug delivery. (August 2020) - Guo, Zhiheng; Yang, Yi; Shu, Yang; Qiao, Li; Peng, Min; Wang, Zhenpeng
Nanodrug delivery systems have been widely researched to achieve efficient antitumor drug delivery. However, the controlled drug delivery at tumor cells remains the main challenge for antitumor therapy. Herein, a pH and reduction-responsive nanocarrier based on green tea polyphenols was employed as a smart excipient for chemotherapy drug delivery. Paclitaxel, as a chemotherapy drug, was loaded in the nanocarrier, noted as green tea polyphenol/paclitaxel. The green tea polyphenol/paclitaxel kept constant diameter at physiological condition (i.e. pH 7.4), while gradually enlarged at acid environment (pH = 5.5) and the reductive environment. The in vitro paclitaxel release results indicated that the release of paclitaxel from the green tea polyphenol/paclitaxel at pH 7.4 was slow, whereas obviously accelerated at the acid environment (pH = 5.5) and the reductive environment. The in vitro antitumor assay showed more efficient tumor cells inhibition of green tea polyphenol/paclitaxel than free paclitaxel. Meanwhile, due to the proper size (∼100 nm), green tea polyphenol/paclitaxel could effectively accumulate at tumor sites. In the in vivo mice bearing A549 xenograft mouse models, green tea polyphenol/paclitaxel exhibited satisfactory antitumor effect and depressed system toxicity when compared with free paclitaxel, owing to the enhanced paclitaxel accumulation and controlled paclitaxel release in the tumor cells. With simple compositions and satisfactory antitumor effects, this green tea polyphenol-based nanocarrier can be a promising nanodrug delivery system for the therapy of cancers.